INFLUENCE OF WHEAT BRAN ADDITION AND OF THERMOPLASTIC EXTRUSION PROCESS PARAMETERS ON PHYSICAL PROPERTIES OF CORN-BASED EXPANDED EXTRUDED SNACKS - Reinaldo Eduardo FERREIRA (Alimentos e Nutrição, 2011)
Corn-based expanded extruded snacks containing wheat bran as dietary fiber source were evaluated with respect to instrumental hardness, expansion index and color (L* - lightness). Internal cell structure was observed through Scanning Electron Microscopy (SEM). Snacks were produced following a 23 complete factorial design, in a single screw extruder (model GNF 1014/2, BRABENDER, Germany). The three independent variables studied were: moisture (from 16.3 to 29.7%); temperature of the 2nd and 3rd extruder zones (from 104.8 to 155.2ºC); and wheat bran content (from 0 to 24.6%). An increase in temperature resulted in lower extrudate hardness values, which varied from 1.6 to 4.8kgf. Higher moisture and lower wheat bran contents resulted in snacks with greater hardness. Expansion index, that varied from 1.7 to 3.7, was mainly influenced by moisture and temperature, being that higher moisture values combined to higher temperatures resulted in lower expansion indexes. The snacks presented lightness (L*) values between 42.77 and 64.41, being the temperature the variable that most influenced the values, because higher values of temperature resulted in higher L* values. Observing the snacks through Scanning Electron Microscopy, the influence of wheat bran could be observed, as higher contents of wheat bran contributed to the formation of cells with reduced sizes. During the sensory analysis, snacks with and without wheat bran, optimum and control, respectively, produced under the same temperature (130°C) and moisture (23%) were compared. Snacks were evaluated by 40 judges through an acceptance test, using a 9-point hedonic scale (mixed structured), in relation to color, appearance, texture (hardness), taste and global evaluation. Optimum and control snacks differed significantly at 95% significance, with the best acceptance for all attributes being obtained for the control.